2010
DOI: 10.1111/j.1574-6968.2010.01973.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of subinhibitory concentrations of licochalcone A on the secretion of enterotoxins A and B by Staphylococcus aureus

Abstract: Enterotoxins produced by Staphylococcus aureus are the key pathogenicity factors that can cause a variety of illnesses in humans, including staphylococcal gastroenteritis and food poisoning. It has been proven that licochalcone A is a potentially effective antimicrobial agent against S. aureus. In this study, Western blot assays, tumour necrosis factor release assays, murine T-cell proliferation assays, and real-time reverse transcriptase-PCR were performed to evaluate the effect of subinhibitory concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…Decreased secretion of enterotoxins was also noted [129]. Real-time polymerase chain reaction (PCR) indicated that these effects were accompanied by a decrease in transcription of the agrA gene, suggesting that the observed results may actually be due to inhibition of virulence factor synthesis rather than virulence factor secretion [39,129]. In light of these PCR results, and the recent demonstration that epicatechin gallate binds predominantly to the cytoplasmic membrane [102], it seems plausible that the above flavonoids may interfere with AgrC (a cytoplasmic membrane-associated [108] quorum-sensing signal receptor found in S. aureus).…”
Section: Inhibition Of Virulence Factor Secretionmentioning
confidence: 93%
See 1 more Smart Citation
“…Decreased secretion of enterotoxins was also noted [129]. Real-time polymerase chain reaction (PCR) indicated that these effects were accompanied by a decrease in transcription of the agrA gene, suggesting that the observed results may actually be due to inhibition of virulence factor synthesis rather than virulence factor secretion [39,129]. In light of these PCR results, and the recent demonstration that epicatechin gallate binds predominantly to the cytoplasmic membrane [102], it seems plausible that the above flavonoids may interfere with AgrC (a cytoplasmic membrane-associated [108] quorum-sensing signal receptor found in S. aureus).…”
Section: Inhibition Of Virulence Factor Secretionmentioning
confidence: 93%
“…Decreased secretion of enterotoxins was also noted [129]. Real-time polymerase chain reaction (PCR) indicated that these effects were accompanied by a decrease in transcription of the agrA gene, suggesting that the observed results may actually be due to inhibition of virulence factor synthesis rather than virulence factor secretion [39,129].…”
Section: Inhibition Of Virulence Factor Secretionmentioning
confidence: 94%
“…The growth curves were tested by the method described by Qiu et al (Qiu et al, 2010), with minor exceptions. Briefly, C. sakazakii strain ATCC 29544 was grown to an OD 600 value of 0.2 in TSB, whereupon 125 mL of the culture was transferred into each well on 96-well microtiter plates.…”
Section: Growth Curvesmentioning
confidence: 99%
“…Because of their potent antimicrobial properties against a broad spectrum of microorganisms such as S. aureus, Salmonella, and Listeria monocytogenes, plant extracts, especially phytochemicals they contain, have gained great interest (Cowan, 1999;Carson et al, 2006). Many studies have been reported that natural extracts such as oil, licochalcone A, and eugenol have an antimicrobial function (Burt, 2004;Qiu et al, 2010aQiu et al, , 2010b.…”
Section: Introductionmentioning
confidence: 99%